Assessment and monitoring of spatio-temporal changes in Keoladeo Ghana National Park, Rajasthan, India using geoinformatics - Reddy, C Sudhakar; Krishna, P Hari; Swetha, V; Shivakala, T; Charan, Prabhu D (Journal of Wetlands Ecology, 2011)
Knowledge of changes in wetlands is becoming a very important issue for sustainable management of natural resources. The present work has been carried out: in Keoladeo Ghana National Park (KNP), a RAMSAR site to study the dynamics of wetlands with reference to long-term and seasonal changes in extent of water spread, vegetation types and to build a spatial database on wetlands. Multi-temporal satellite data of Landsat MSS (1977), Landsat TM data (1989), IRS P6 AWIFS (2005) and IRS P6 LISS III data (2005-2006) was used for mapping and spatial analysis. Comparisons between 1977 and 2005 indicated that changes in overall wetland areas were significant. The total area of wetland in March 1977 was 186 hectares and in March 2005 it was found to be 7.5 ha. There is a drastic reduction in spatial extent of water spread from October to May and results indicated that the total area ranged from 528 ha (October 2005) to 7.5 ha (March-May 2005). The study clearly points that Geoinformatics have become very effective tool for wetlands mapping and monitoring. Key words: wetlands; geoinformatics; satellite data; Keoladeo; Rajasthan DOI: 10.3126/jowe.v4i0.3115 Journal of Wetlands Ecology, (2010) Vol. 4, pp 33-42